2021
DOI: 10.1002/hup.2782
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study assessing the brain gauge as an indicator of cognitive recovery in alcohol dependence

Abstract: Alcohol dependence (AD) is associated with multiple cognitive deficits, which can affect treatment outcomes. Current measures of tracking brain recovery (e.g., functional magnetic resonance imaging) can be less accessible for practitioners. This study pilots a novel device (the brain gauge; BG) to assess its utility, and track recovery of cognitive function in residential alcohol treatment. Methods: A repeated measures design assessed changes in cognitive function during detoxification. Twenty‐one participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Previous research using such a device has highlighted alcohol-related differences and changes in cognitive function, indicating that this technology has potential use in this field ( Nguyen et al, 2013 ; Powell et al, 2021 ). Indeed, a pilot study by Powell et al (2021) found that Brain Gauge composite scores most sensitive to early treatment were largely those using RT tasks. Understanding RT change during early recovery and how this compares to the ‘normal’ function (of controls) will contribute to our understanding of treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using such a device has highlighted alcohol-related differences and changes in cognitive function, indicating that this technology has potential use in this field ( Nguyen et al, 2013 ; Powell et al, 2021 ). Indeed, a pilot study by Powell et al (2021) found that Brain Gauge composite scores most sensitive to early treatment were largely those using RT tasks. Understanding RT change during early recovery and how this compares to the ‘normal’ function (of controls) will contribute to our understanding of treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we used vibrotactile presentation with response via computer mouse to identify alcohol-related changes in processing speed during early residential detox in individuals with an AUD ( Powell et al, 2021b ). This approach also identified differences in the ability to discriminate between different amplitudes in heavy and light drinkers ( Nguyen et al, 2013 ) and in young (aged 18–26 years) drinkers, and therefore appears sensitive to alcohol-related cognitive changes.…”
Section: Introductionmentioning
confidence: 99%